An Induced Mutation in HvRECQL4 Increases the Overall Recombination and Restores Fertility in a Barley HvMLH3 Mutant Background - Arrieta, Mikel; Macaulay, Malcolm; Colas, Isabelle; Schreiber, Miriam; Shaw, Paul D.; Waugh, Robbie; Ramsay, Luke (Frontiers in Plant Science, 2021)
Plant breeding relies on meiotic recombination or crossing over to generate new combinations of alleles along and among chromosomes. However, crossing over is constrained in crops like barley by a combination of low frequency and biased distribution. Here we attempted to identify genes that limit recombination by performing a suppressor screen for restoration of fertility to the semi-fertile barley mutant desynaptic10 (des10), carrying a mutation in the barley orthologue of MutL-Homolog 3 (HvMlh3) a member of the MutL-homolog (MLH) family of DNA mismatch repair genes. des10 mutants exhibit reduced recombination and fewer chiasmata, resulting in the loss of obligate crossovers (CO) leading to chromosome mis-segregation. Here we identified several candidate suppressor lines and confirmed their restored fertility in an Hvmlh3 background in subsequent generations. We focus here on one of the candidate suppressor lines, SuppLine2099, which showed the most complete restoration of fertility. We characterised this line using a target sequence (TENSEQ) capture array representing barley orthologues of forty-six meiotic genes. We found that SuppLine2099 contained a C/T change in the anti-crossover gene RECQL4 resulting in the substitution of a non-polar Glycine to a polar Aspartic acid (G700D) amino acid in the conserved helicase domain. SNP genotyping of F3 populations revealed nearly double the recombination levels in homozygous Hvrecql4 lines compared to the wildtype. Intriguingly, the effect of Hvrecql4 in an Hvmlh3 background was further enhanced, more than quadrupling the recombination frequency observed in Hvmlh3 homozygotes alone. However, we did not observe a significant change to the distribution of CO events. Our results confirm the anti-CO role of RECQL4 in a large genome cereal and establish the possibility of testing the utility of increasing recombination in the context of traditional crop improvement.